‘Northern problem’: Postcolony, identity and political [in]stability in cote d’ivoire and togo - Matereke, K.; Salihu, N. (Bondage of Boundaries and Identity Politics in Postcolonial Africa: The 'Northern Problem' and Ethno-Futures, 2013)
100 ‘Northern problem’ Postcolony, identity and political [in]stability in Cote d’Ivoire andTogo Kwesi Aning and Naila Salihu INTRODUCTION Colonialism bequeathed African states with contested and conflict-generating legacies, rooted in problematic boundaries, fragmented identities and the fragile nature of the postcolony. These legacies cut through territories inhabited by different indigenous peoples and societies with varied internal diversities, and arbitrarily amalgamated a diversity of communities into uneasy administrative , political, economic, social and cultural structures or colonial states (Welsh 1996; Mbembe 2001). Analyses abound on how African political boundaries were arbitrarily drawn for the purposes of administrative convenience or as a result of territorial trade-offs among imperial powers. In most parts of Africa, heterogeneous groups marked by different nations, ethnicidentities,kinshipties,classes,religions,languagegroups,races,cultures and geographic locations, were forced to live together within the boundaries of the postcolonial nation-states. As a result of the cavalier construction of colonial borders, the postcolonial successor regimes inherited caricatured territorial entities that were made up of distinct and sometimes hostile ethnic groups and in some instances divided homogeneous ethnic communities into two or more states (Ayoob 1995). These boundaries, irrespective of their arbitrariness, were deemed inviolable by independent African states through the Organisation of African Unity (OAU). Indeed the arbitrary boundaries were used as part of the pan-Africanist agenda. It is no wonder why, Africa’s new elites who ascended to power as a result of decolonisation processes decided to accept, consolidate and exploit these balkanised states. What is surprising is that while there is scarcely any African state without boundaries-related problems, the issues of inclusion/exclusion have not opened serious internal African debate even where violent outcomes are manifest (Dorman et al., 2007; Adebajo 2010). Both Cote d’Ivoire andTogo share similar political and socio-economic experiences. Both countries have diverse ethno-religious groups or societies that coexist in the modern state. Following independence from French colonialism in the 1960s, successive leaders CHAPTER 5 101 ‘NORTHERN PROBLEM’ IN COTE D’IVOIRE AND TOGO in both countries have pursued varied policies with mixed outcomes relating to political stability and social cohesion. On one hand Côte d’Ivoire was once touted as the beacon of economic growth and political stability in a troubled West African sub-region. The country ’s remarkable economic growth and political developments in the first two decades of independence was often termed as the ‘African Miracle’ (Langer 2011). Politicisation of identity and citizenship by successive political elites, particularly with the introduction of the concept of Ivoirité, which sought to construct an Ivorian identity that questioned the citizenship rights of most Northerners eventually plunged the country into an internecine political crisis. A failed coup d’etat in 2002 resulted in a bloody civil war, which effectively split the country into a rebel-held north and a government-controlled south. Though the period of active warfare was relatively short, it resulted in more than 1000 battle deaths, and several civilian casualties and human suffering. The quest for sustainable peace and stability remains elusive despite several efforts by the international community to facilitate this. Particularly, after several postponements, presidential elections held in October/November 2010 were considered a milestone towards consolidating democratic peace and stability in the country. However, disputes about the outcomes of elections which are deeply rooted in the ‘northern problem’ brought the country to the brink of another devastating conflict. Violent conflicts, particularly reprisal attacks by loyalist militias of both Laurent Gbagbo and Alasane Ouattara were reported in different parts of the country after the forceful removal of Laurent Gbagbo. This is a glaring manifestation of the ‘northern problem’ which, like a volcano, could explode in future if not constructively managed. Since independence, the political landscape of Togo has been one of political upheavals or violence, human rights abuses, politically-motivated murders and economic decline. Politicisation and discrimination on the basis of ethnicity or identity is prohibited by Togolese Constitution. Nonetheless, the phenomenon is very pervasive and practiced by members of almost all ethnic groups as well as political elites. Although the country has not witnessed any large scale civil war, it remains relatively fragile. The existence of real or imagined politicisation or discrimination of identity, culminating into the near existence of a north-south divide, particularly the Ewe-dominated South and northern ethnic groups such as Kabiye has been a major source of political tension in the country, often escalating into intermittent political violence with a clearly interethnic character. This chapter undertakes a...
Keywords: togo; ivory coast; political unrest